Dynamic Compressive Loading Improves Cartilage Repair in an In Vitro Model of Microfracture: Comparison of 2 Mechanical Loading Regimens on Simulated Microfracture Based on Fibrin Gel Scaffolds Encapsulating Connective Tissue Progenitor Cells. Issue 9 (July 2019) - Iseki, Tomoya; Rothrauff, Benjamin B.; Kihara, Shinsuke; Sasaki, Hiroshi; Yoshiya, Shinichi; Fu, Freddie H.; Tuan, Rocky S.; Gottardi, Riccardo
Background: Microfracture of focal chondral defects often produces fibrocartilage, which inconsistently integrates with the surrounding native tissue and possesses inferior mechanical properties compared with hyaline cartilage. Mechanical loading modulates cartilage during development, but it remains unclear how loads produced in the course of postoperative rehabilitation affect the formation of the new fibrocartilaginous tissue. Purpose: To assess the influence of different mechanical loading regimens, including dynamic compressive stress or rotational shear stress, on an in vitro model of microfracture repair based on fibrin gel scaffolds encapsulating connective tissue progenitor cells. Study Design: Controlled laboratory study. Methods: Cylindrical cores were made in bovine hyaline cartilage explants and filled with either (1) cartilage plug returned to original location (positive control), (2) fibrin gel (negative control), or (3) fibrin gel with encapsulated connective tissue progenitor cells (microfracture mimic). Constructs were then subjected to 1 of 3 loading regimens: (1) no loading (ie, unloaded), (2) dynamic compressive loading, or (3) rotational shear loading. On days 0, 7, 14, and 21, the integration strength between the outer chondral ring and the central insert was measured with an electroforce mechanical tester. The central core component, mimicking microfracture neotissue, was also analyzed for gene expression by real-time reverse-transcription polymerase chain reaction, glycosaminoglycan, and double-stranded DNA contents, and tissue morphology was analyzed histologically. Results: Integration strengths between the outer chondral ring and central neotissue of the cartilage plug and fibrin + cells groups significantly increased upon exposure to compressive loading compared with day 0 controls ( P = .007). Compressive loading upregulated expression of chondrogenesis-associated genes (SRY-related HGMG box-containing gene 9 [ SOX9 ], collagen type II α1 [ COL2A1 ], and increased ratio of COL2A1 to collagen type I α1 [ COL1A1 ], an indicator of more hyaline phenotype) in the neotissue of the fibrin + cells group compared with the unloaded group at day 21 ( SOX9, P = .0032; COL2A1, P < .0001; COL2A1:COL1A1, P = .0308). Fibrin + cells constructs exposed to shear loading expressed higher levels of chondrogenic genes compared with the unloaded condition, but the levels were not as high as those for the compressive loading condition. Furthermore, catabolic markers ( MMP3 and ADAMTS 5 ) were significantly upregulated by shear loading ( P = .0234 and P < .0001, respectively) at day 21 compared with day 0. Conclusion: Dynamic compressive loading enhanced neotissue chondrogenesis and maturation in a simulated in vitro model of microfracture, with generation of more hyaline-like cartilage and improved integration with the surrounding tissue. Clinical Relevance: Controlled loading after microfracture may be beneficial in promoting the formation of more hyaline-like cartilage repair tissue; however, the loading regimens applied in this in vitro model do not yet fully reproduce the complex loading patterns created during clinical rehabilitation. Further optimization of in vitro models of cartilage repair may ultimately inform rehabilitation protocols.